The Role of Advocate in the Mediation Process of Divorce Cases at the Religious Court of Sidrap - Wiwin, Wiwin (Jurnal Litigasi Amsir, 2024)
This article discusses the role of attorneys in the process of mediating divorce cases at the Sidrap Religious Court. This study aims to determine the role of attorneys in providing legal assistance in the mediation process of divorce cases so that mutually beneficial agreements are reached for both parties. This study used field research methods with descriptive qualitative through observation, interviews, and documentation studies. The results of this study indicate: First, the role of attorneys in the mediation process of divorce cases at the Sidrap Religious Court is to assist/represent and protect the interests of clients, facilitate effective communication, provide appropriate legal advice, and assist in reaching mutually beneficial agreements for both side. Second, the factors that influence the role of legal counsel in the Mediation Process of Divorce Cases at the Sidrap Religious Court are influenced by two factors, 1). Supporting factors that can influence the role and effectiveness of legal counsel are the legal factors themselves (laws), law enforcement factors, facilities or facilities that support law enforcement, community factors, and cultural factors. 2). Inhibiting factors that influence attorneys in the process of mediating divorce cases at the Sidrap Religious Court, namely community factors or the client itself. Third, the role of attorneys in the mediation process of divorce cases at the Islamic Religious Courts is based on the principles of Islamic family law, namely by understanding and applying the principles of Islamic family law in the mediation process.